Microbiota Variation Across Life Stages of European Field-Caught Anopheles atroparvus and During Laboratory Colonization: New Insights for Malaria Research - Birnberg, Lotty; Climent-Sanz, Eric; Codoñer, Francisco M.; Busquets, Núria (Frontiers in Microbiology, 2021)
The potential use of bacteria for developing novel vector control approaches has awakened new interests in the study of the microbiota associated to vector species. To set a baseline for future malaria research, high-throughput sequencing of the bacterial 16S ribosomal gene V3-V4 region was used to profile the microbiota associated to late instar larvae, newly emerged females, and wild-caught females of a sylvan Anopheles atroparvus population from a former malaria transmission area of Spain. Field-acquired microbiota was then assessed in non-blood fed laboratory-reared females from the second, sixth and tenth generations. Diversity analyses revealed that bacterial communities varied and clustered differently according to origin with sylvan larvae and newly emerged females distributing closer to laboratory-reared females than to their field counterparts. Inter-sample variation was mostly observed throughout the different developmental stages in the sylvan population. Larvae harbored the most diverse bacterial communities whilst wild-caught females, the poorest. In the transition from the sylvan environment to the first time point of laboratory breeding, a significant increase in diversity was observed, although this did decline under laboratory conditions. Despite diversity differences between wild-caught and laboratory-reared females, a substantial fraction of the bacterial communities was transferred through transstadial transmission and these persisted over ten-laboratory generations. Differentially abundant bacteria were mostly identified between breeding water and late instar larvae, and in the transition from wild-caught to laboratory-reared females from the second generation. Our findings confirmed the key role of the breeding environment in shaping the microbiota of An. atroparvus. Gram-negative bacteria governed the microbiota of An. atroparvus with the prevalence of proteobacteria. Pantoea, Thorsellia, Serratia, Asaia, and Pseudomonas dominating the microbiota associated to wild-caught females, with the latter two governing the communities of laboratory-reared females. A core microbiota was identified with Pseudomonas and Serratia being the most abundant core genera shared by all sylvan and laboratory specimens. Overall, understanding microbiota composition of An. atroparvus and how this varies throughout the mosquito life cycle and laboratory-colonization, paves the way when selecting potential bacterial candidates for use in microbiota-based intervention strategies against mosquito vectors, thereby improving our knowledge of laboratory-reared An. atroparvus mosquitoes for research purposes.